Non-cell autonomous and non-catalytic activities of ATX in the developing brain - Greenman, Raanan; Gorelik, Anna; Sapir, Tamar; Baumgart, Jan; Zamor, Vanessa; Segal-Salto, Michal; Levin-Zaidman, Smadar; Aidinis, Vassilis; Aoki, Junken; Nitsch, Robert; Vogt, Johannes; Reiner, Orly (Frontiers in Neuroscience, 2015)
The intricate formation of the cerebral cortex requires a well-coordinated series of events, which are regulated at the level of cell-autonomous and non-cell autonomous mechanisms. Whereas cell-autonomous mechanisms that regulate cortical development are well-studied, the non cell-autonomous mechanisms remain poorly understood. A non-biased screen allowed us to identify Autotaxin (ATX) as a non cell-autonomous regulator of neural stem cell proliferation. ATX (also known as ENPP2) is best known to catalyze lysophosphatidic acid (LPA) production. Our results demonstrate that ATX affects the localization and adhesion of neuronal progenitors in a cell autonomous and non-cell autonomous manner, and strikingly, this activity is independent from its catalytic activity in producing LPA.